Conflict in Fourteenth-Century Iberia - Kagay, Donald J., author.
1 online resource.
Keywords: "In Conflict in Fourteenth-Century Iberia, Kagay and Villalon trace the complicated economic military, political, and social background of the relationship of Iberia's two greatest Christian states of the fourteenth century, Castile and the Crown of Aragon and their rulers, Pedro I (r. 1350-1366/69) and Pere III (r. 1336-1387). Besides chapters discussing the War of the Two Pedros (1356-1366) and the Castilian Civil War (1366-1369), the authors provide extended treatments of the strategical and tactical elements of the conflicts, the parliamentary, diplomatic, and governmental developments that occurred because of the conflicts as well as their social and political aftermaths. This work, along with authors' earlier book on the battle of Nájera (1367) provides a much-needed review of Iberia's violent fourteenth century"--